2014
DOI: 10.1155/2014/341826
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic Factors in Acute Methadone Toxicity: A 5-Year Study

Abstract: Background. Delayed or recurrent profound respiratory depression, ventricular dysrhythmias, acute lung injury, and death are the major complications of MTD overdose. We aimed to clarify the prognostic factors in MTD toxicity. Materials and Methods. Retrospectively, medical files of all patients poisoned by MTD and older than 12 years of age who had presented to Loghman Hakim Poison Center between 2007 and 2012 were evaluated. The data was compared between survivors and nonsurvivors. Results. Twenty-eight out o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
20
0
3

Year Published

2016
2016
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 20 publications
(26 citation statements)
references
References 18 publications
3
20
0
3
Order By: Relevance
“…Renal failure is an important cause of mortality and morbidity related to methadone toxicity (Corkery et al 2004; Aghabiklooei et al 2014), and rhabdomyolysis is responsible for most cases of AKI following methadone abuse. One of the debates on this topic is the unclear mechanism involved in methadone-induced rhabdomyolysis and AKI (Hojs and Sinkovič 1992).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Renal failure is an important cause of mortality and morbidity related to methadone toxicity (Corkery et al 2004; Aghabiklooei et al 2014), and rhabdomyolysis is responsible for most cases of AKI following methadone abuse. One of the debates on this topic is the unclear mechanism involved in methadone-induced rhabdomyolysis and AKI (Hojs and Sinkovič 1992).…”
Section: Discussionmentioning
confidence: 99%
“…In Iran and Australia, the main clinical replacement for opioid dependence is methadone syrup (Aghabiklooei et al 2014; Pilgrim et al 2013). …”
Section: Methadone Pharmacokineticsmentioning
confidence: 99%
See 2 more Smart Citations
“…A case file study has suggested that methadone can increase QTc interval that makes methadone users vulnerable to malignant cardiac arrhythmias [116]. Methadone toxicity-induced death was associated with renal failure while respiratory failure was the leading cause of death [117]. When methadone is consumed along with other drugs it becomes hard to ascertain whether methadone overdose is the lead cause of death [118].…”
Section: Methadonementioning
confidence: 99%